Сучасний український текстиль: еволюція, досвід, перспективи - Кусько, Г. (Студії мистецтвознавчі, 2009)
Modern Ukrainian artistic textile was formed under influence of fiber art movement. Now is high time to refresh main steps of the process, sum results and model future. Souses, terminology, trends and pioneers of art fabric movement were examined in articles, published during former years (since 1993) by author of this publication. Number of articles was dedicated to Ukraine Biennale of nontraditional textiles «Textile Madness». The article rebirth in mind the main periods of development of new textiles in Ukraine, role of artistic pedagogic – especially efforts of lecturers of L’viv State Institute of Applied and Decorative Art (now L'viv National Academy of Arts). Semester and diploma works, marked by new trends, are named in the article. Lectures «Textiles in Art. Views of artists of XX century», read in L’viv Academy of Arts by Swiss lecturer Hannes Shupbach, were among stimulus of innovative textiles in L’viv, as well as participation of Ukrainian artists in special textile exhibitions in Ukraine and abroad. First of all that's: First Ukrainian Exhibition of Chamber Textiles, L’viv (1989-1990); Ukraine Biennale of nontraditional textiles «Textile Madness», L’viv (started in 1997); Triennial of Artistic Textiles of Ukraine, Kyiv (started in 2004); International Youth Symposium ArcheThreadNovo, L’viv (2006). Modern practice needs new rates. Pieces, which seamed recently innovative, today are not. Modern exhibitions need equal presentation of all trends and techniques. Future projects must be intrigue and attractive.